PERSPECTIVE OF THEORY WORK OF ADJUSTMENT AND ITS IMPLEMENTATION IN CAREER GUIDANCE AND COUNSELING - Yuliani Pertiwi; Mega Iswari; Daharnis (Yayasan Citra Dharma Cindekia, 2022)
Each individual has different abilities and skills and the work environment also has various differences. The more appropriate the existing requirements of the individual with the demands of the existing requirements in the work environment, the higher the satisfaction obtained. A person will work happily and joyfully if what he does is in accordance with his circumstances, abilities and interests. On the other hand, if a person works not in accordance with what is in him, it can be ascertained that he will be less enthusiastic at work, less happy, and less diligent. To lead to that. For this reason, career guidance is needed, career guidance can be done using the theory work of adjustment approach . The theory work of adjustment includes a class of theories known as P ( parson ) and E ( environment ) theories as well as the subject of adjustment between P and E interactions.